Systematic Layout Planning to Improve Facility Layout in Small and Medium Food Enterprise - Febriani, Falentina; Wurjaningrum, Febriana (Southeast Asian Business Review, 2024)
The absence of a structured method for revamping current or introducing new production layouts in small and medium-sized enterprises may hinder the flexibility and competitiveness of the enterprise. This study aimed to assess the existing production layout and offer improvement recommendations for a small and medium-sized food enterprise in East Java, Indonesia. Data was obtained through interviews with the owner and observation at the production site. The research employed systematic layout planning, utilizing activity relationship charts and diagrams. The findings presented two alternative suggestions for the production facility layout, with the study recommending the second alternative based on an evaluation of criteria. The second proposed alternative exhibited a total material handling distance per week of 1,812 and a total material handling cost of 17,961.96 rupiah, lower than the first proposed alternative. The managerial implications of this study pertain to the construction of facilities with a focus on technical and hygiene requirements, the design and layout of buildings and rooms, and the requirements for machinery, equipment, and transportation to ensure product quality and safety.